A Dynamic Model for Direct and Indirect Matrix Converters. (8th April 2014) - Hosseini Abardeh, Mohamad; Ghazi, Reza
Abstract : The complicated modulation algorithm and the high switching frequency are two main hindrances in the analysis and simulation of matrix converters (MCs) based systems. To simplify the analysis and accelerate the simulation of MCs, a unique dynamic model is presented for the MC, which is independent of MC type (direct or indirect) and the modulation algorithm. All the input and output variables are transferred to the respective reference frames and their relations and limits are calculated. Based on the proposed equations, an equivalent circuit model is presented which can predict all the direct and indirect matrix converters dynamic and steady state behaviors without the need for small simulation time steps. Validity of the proposed model is evaluated using simulation of the precise model. Moreover, experimental results from a laboratory matrix converter setup are provided to verify the accuracy of the simulation results.